Zinc Deficiency, Carbonic Anhydrase, and Photosynthesis in Leaves of Spinach - Randall, P. J. (1973)
A shortage in the zinc supply to spinach (Spinacia oleracea L.) drastically reduced carbonic anhydrase levels with little effect on net CO(2) uptake per unit leaf area, except with the most severe zinc stresses. Under these conditions, carbonic anhydrase was below 10% and photosynthesis 60 to 70% of the control levels. When photosynthesis was measured at a range of CO(2) supply levels, zinc-deficient leaves were less efficient at 300 to 350 microliters per liter CO(2) and above, but the same as controls at lower CO(2) levels. This suggests that carbonic anhydrase does not affect the diffusion of CO(2), and that the effect of zinc deficiency was on the photosynthetic process itself. Our evidence does not support the hypothesis that carbonic anhydrase has some role in facilitating the supply of CO(2) to the sites of carboxylation within the chloroplast.